2017
DOI: 10.1155/2017/8524073
|View full text |Cite
|
Sign up to set email alerts
|

Oenological and Quality Characteristic on Young White Wines (Sauvignon Blanc): Effects of High Hydrostatic Pressure Processing

Abstract: High hydrostatic pressure (HHP) has shown to have an effect of enhancing some properties without detrimental effects on important quality characteristics, such as colour, pH, and turbidity. This suggests that this technique can be used as an alternative to the existing methods used in wine industry processing. The aim of this study was to investigate the effects of HHP on aroma compounds and also sensory and quality properties of young white wine. HHP treatment did not influence physicochemical parameters, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Overall, as already observed in the case of red wine, the lowest content of analyzed phenolic compounds in the white wine was also determined after treatment at 600 MPa for 25 min. Similar results were reported by Briones-Labarca et al [ 19 ], whose study showed that the total phenolic and flavonoid contents of young white wine were not severely reduced by HHP treatments (300–500 MPa/5–15 min). Moreover, Santos et al [ 12 ] found that HHP treatments (425 and 500 MPa for 5 min) had no effect on the total phenolics and antioxidant activity of white wine immediately after processing.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, as already observed in the case of red wine, the lowest content of analyzed phenolic compounds in the white wine was also determined after treatment at 600 MPa for 25 min. Similar results were reported by Briones-Labarca et al [ 19 ], whose study showed that the total phenolic and flavonoid contents of young white wine were not severely reduced by HHP treatments (300–500 MPa/5–15 min). Moreover, Santos et al [ 12 ] found that HHP treatments (425 and 500 MPa for 5 min) had no effect on the total phenolics and antioxidant activity of white wine immediately after processing.…”
Section: Resultssupporting
confidence: 91%
“…Santos et al [ 12 ] also observed the decrease of the total phenolic content as well as antioxidant activity in pressurized white wine samples after 12 months of storage. It is suggested that the generation of highly reactive radicals during HHP processing and enhancement of oxidation and polymerization reactions of phenolic compounds are responsible for reduction in their content [ 9 , 12 , 19 , 42 ]. Concerning the effect of antioxidant treatments (SO 2 and GSH), the pressurized low SO 2 wine showed the lowest content of analyzed phenolics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant increases in pH and decreases in TA ( p < 0.05) after processing were of slight extension. Similarly, Briones Labarca et al, (2017) reported that after HHP treatments (300–500 MPa, at 5–15 min in the absence of chips), Sauvignon Blanc wines exhibited physicochemical properties similar to the untreated wine [ 37 ]. On day 90, no differences were found between treatments (B, HHP, M, T) for all parameters analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…High hydrostatic pressure (HHP) is an emerging nonthermal and environmentally friendly food processing technology. Materials to be processed are exposed to 400-600 MPa (58-87,000 psi) conditions for certain amount of time at room temperature [8,9]. is increases the mass transfer rate, e ciently damages cell membranes, enhances solvent permeability, and improves production e ciency.…”
Section: Introductionmentioning
confidence: 99%